The Patriot Act “Mangilik El” – Scientific and Expert Support - Shaukenova, Z (Public Administration and Civil Service, 2016)
The article examines the impact of social and political changes taking place in the conditions of democratization of society, the formation of human and national values, the originality of which was the subject of a special political analysis . In today’s globalization and the process of entering our country among the developed countries of the world attention is drawn to the problems of improving the national values and ideas In this regard, the President of NA real challenges for Kazakhstan society on the road to implementation of the five presidential reform program “100 concrete steps”, in which the necessity of preparing a draft of the Patriot Act and the national idea “MANGILIK EL” ( “Eternal People”) were nominated Nazarbayev The future of the nation and the people, based on a system of certain values, it is necessary to create, in accordance with the priorities of the development of competitive countries of the world and the strategic development of innovative models . This important task to the value orientations of society unites and unites people in flowing political processes and determines the formation of patriotic nation, brought up on national values . Thus, in the state, each citizen is necessary to establish such values as unity, integrity and independence of Kazakhstan, social stability and political harmony and others